Antigenic Challenge Influences Epigenetic Changes in Antigen-Specific T Regulatory Cells - Iwaszkiewicz-Grzes, Dorota; Piotrowska, Magdalena; Gliwinski, Mateusz; Urban-Wójciuk, Zuzanna; Trzonkowski, Piotr (Frontiers in Immunology, 2021)
Background: Human Tregs are the fundamental component of the immune system imposing immune tolerance via control of Teffs. Ongoing attempts to improve Tregs function have led to the creation of a protocol that produces antigen-specific Tregs, when polyclonal Tregs are stimulated with monocytes loaded with antigens specific for type 1 diabetes. Nevertheless, the efficiency of the suppression exerted by the produced Tregs depended on the antigen with the best results when insulin β chain peptide 9-23 was used. Here, we examined epigenetic modifications, which could influence these functional differences. Methods: The analysis was pefromed in the sorted subsets of Tregs and Teffs (POLY, SPEC, UNSPEC) generated by the stimulation with monocytes loaded with either whole insulin (INS) or insulin β chain peptide 9-23 (B:9-23) or polyclonal cells (POLY). A relative expression of crucial Tregs genes was determined by qRT-PCR. The TSDR in foxP3 gene methylation levels were assessed by qMSP. ELISA was used to measure genome DNA methylation and histone H3 post-translational modifications (PTMs). Results: Tregs SPECB:9-23 was the only subset expressing all assessed crucial genes necessary for regulatory function with the highest level of expression among all analysed conditions. The methylation of global DNA as well as TSDR were significantly lower in Tregs SPECB:9-23 than in Tregs SPECINS. When compared to Teffs, Tregs were characterized by a relatively lower level of PTMs but it varied in respective Tregs/Teffs pairs. Importantly, whenever the difference in PTM within Tregs/Teffs pair was significant, it was according to the scheme in which the level was always low in one subset from the pair and high in the other. It was always low in Tregs SPECINS and high in Teffs SPECINS, it was high in Tregs UNSPECINS and low in Teffs UNSPECINS. There were no differences in Tregs/Teffs SPECB:9-23 pair and the level of modifications was low in Tregs UNSPEC B:9-23 and high in Teffs UNSPEC B:9-23. Conclusions: Whole insulin and insulin β chain peptide 9-23 affected differently epigenetic changes in CD4+ T cells, when presented by monocytes. The peptide preferably favored specific Tregs, while whole insulin activated both Tregs and Teffs.